2015
DOI: 10.1590/s1413-65382115000100008
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de Ensino e Recursos Pedagógicos para o Ensino de Alunos com TDAH em Aulas de Educação Física

Abstract: o Transtorno do Déficit de Atenção com Hiperatividade (TDAH) é um transtorno neurocomportamental, multifatorial, comum na população de crianças em idade escolar, cuja característica principal é um padrão persistente de desatenção e ou hiperatividade/impulsividade, que frequentemente resulta em prejuízos emocionais, sociais e sobretudo, funcionais. Nesta perspectiva, a pesquisa teve como objetivo planejar, aplicar e analisar um programa de intervenção, composto por atividades psicomotoras, lúdicas e jogos de es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
8
Order By: Relevance
“…Others studies of psychomotor intervention in individuals with ADHD have shown changing patterns of psychomotor functions, especially spatial organization, balance, fine motor skills, and body schema, with similar results to this study. However, the methods used have been diversified, including equine therapy, physiotherapy, and physical education (Barbosa & Munster, 2014;Costa et al, 2015;Niehues & Niehues, 2014. The method used in this study, through individual psychomotor therapy, was consistent with these methods, as it involves fun activities and was contextualized to the routine of a child, guaranteeing the best compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others studies of psychomotor intervention in individuals with ADHD have shown changing patterns of psychomotor functions, especially spatial organization, balance, fine motor skills, and body schema, with similar results to this study. However, the methods used have been diversified, including equine therapy, physiotherapy, and physical education (Barbosa & Munster, 2014;Costa et al, 2015;Niehues & Niehues, 2014. The method used in this study, through individual psychomotor therapy, was consistent with these methods, as it involves fun activities and was contextualized to the routine of a child, guaranteeing the best compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted with 40 weekly group meetings. Research has shown that the intervention program was favorable for the development of motor and cognitive skills of the students (Costa, Moreira, & Seabra Júnior, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Outro recurso a ser utilizado é o estabelecimento de regras, rotina e uso da mediação, seja dos professores ou auxiliares ou colegas de sala, podem ser utilizadas também atividades grupais, estas propiciam trocas de experiência e desenvolvimento de cooperação entre os alunos (COSTA; MOREIRA; SEABRA JÚNIOR, 2015;SANTOS;MARTINS, 2015).…”
Section: Perspectivas De Professores Sobre Inclusão Escolarunclassified
“…Por isto, devem-se planejar atividades iniciais, para além dos conteúdos acadêmicos, que permitam discutir as características que nos fazem diferentes e semelhantes dos outros, que enfoquem a empatia como o respeito à vez da fala da outra pessoa e estar atento à fala do outro, minimizando a rejeição e solidão vivenciada pelos alunos com NEES (TOLEDO; VITALIANO, 2012;ENUMO;ROSA, 2012;COSTA;MOREIRA;SEABRA JÚNIOR, 2015). Santos e Martins (2015) discutem que tanto atividades intra e extracurriculares contribuem para participação e engajamento de todos os alunos.…”
Section: Categoria Iii: Processo De Ensino -Aprendizagemunclassified
See 1 more Smart Citation